The master and the dean the literary criticism of Henry James and William Dean Howells - Davidson, Rob, 1967- (University of Missouri Press, 2005)
"Comparative study of Henry James's and William Dean Howells's literary criticism. Examines the interrelationship between the men, emphasizing their aesthetic concerns and attitudes toward the market and audience, and their beliefs concerning the moral value of fiction and the United States as a literary subject, and writings about each other"--Provided by publisher.